Medijski pluralizem in dinamika menjav političnih elit - Tomšič, Matevž (Annales. Series historia et sociologia, 2007)
The article deals with the analysis of relationship between the character of the media sphere and political dynamics and the profile of political elite. Media as a framework of social and political communication exert significant influence on development of open and democratic society. Democracy as political system is based on competition between different political actors for support of the citizenry as well as on the balance of power between different political institutions and branches of government. The main thesis of this article is that a certain level of elite circulation, in terms of continuous change on top positions in political space, is necessary for sustained and developed democracy to take place. These changes - or at least the prospect of them - that are related to the existence of feasible alternative to incumbent ruling elite contribute to the maintenance of relative dispersion of power, thus preventing its monopolization by the hand of political group of any kind. Media pluralism is one of the factors that importantly contributes to this elite circulation. It provides different individual and groups with a chance to present their views, ideas and problem-solutions in public on the equal basis what enables the voters to make an informed political choice. Furthermore, it is important for the citizens to have opportunity to get information from different sources. In this regard, the media space should be composed of media providers that follow diverse political and ideological orientations, thus dealing with particular political and social issue form different angles, in order to perform its democratic function. The author shows the connection between the structure of media sphere and dynamics of change on power position on the case of post-communist Slovenia. He argues that weak media pluralism, in terms of prevalence of particular ideological orientations in Slovenian media and political affiliation of most opinion-leaders to particular political camp, contributed to long-term dominant position of this camp in Slovenian political space
Keywords: democracy; demokracija; medijski prostor; pluralizem; politična elita; Slovenia; Slovenija